Schnyder Corneal Dystrophy: A Rare Case Report - Kurtul, Bengi Ece; Elbeyli, Ahmet; Ozarslan Ozcan, Deniz; Ozcan, Sait Coskun; Karaaslan, Abdulkerim (Nepalese Journal of Ophthalmology, 2020)
Introduction: Schnyder corneal dystrophy (SCD) is a rare, autosomal dominant, anterior stromal dystrophy described as progressive bilateral corneal opacification due to abnormal accumulation of cholesterol and phospholipids in the cornea. The clinical signs can change as the patient ages. SCD with different presentations may actually be misdiagnosed. Early diagnosis would help to rule out other potentially sight threatening or treatable conditions like infectious keratitis or drug toxicity. Case: We present a case of a 34-year-old Syrian male patient, came to our clinic for bilateral decreased visual acuity for 5 years. His visual acuity was 0.15 in both eyes. Slitlamp examination revealed corneal arcus or disk-like lesion and polychromatic crystalline depositions in both eyes in subepithelial and the anterior 1/3 of the stroma. The mild onset of arcus lipoides was also seen. Central corneal thickness results were 507 μm in the right eye and 503 μm in the left eye. A diagnosis of Schnyder corneal dystrophy was thought based on clinical presentation and coexistence dyslipidemia of the patient. Conclusion: Ophthalmologists should keep in mind SCD and its associated systemic findings that need to be evaluated and managed properly.